Transplantation of iPSC-TM stimulates division of trabecular meshwork cells in human eyes - Zhu, Wei; Godwin, Cheyanne R.; Cheng, Lin; Scheetz, Todd E.; Kuehn, Markus H. (Scientific reports, 2020)
The trabecular meshwork’s (TM) physiological role is to maintain normal intraocular pressure by regulating aqueous humor outflow. With age, and particularly in eyes with primary open angle glaucoma, the number of cells residing within the TM is markedly decreased and the function of the tissue is compromised. Here we evaluate if transplantation of induced pluripotent stem cell derived TM like cells (iPSC-TM) restores TM cellularity and function in human eyes obtained from older human donors. Human iPSC were differentiated into iPSC-TM and compared to primary TM cells by RNAseq. iPSC-TM were then injected into the anterior segments of human eyes maintained in perfusion culture. Seven and 14 days eyes after injection eyes that received iPSC-TM contained significantly more cells in the TM. Fewer than 1% of all cells appeared to be iPSC-TM, but significantly more cells in these eyes were immunopositive for Ki 67 and incorporated BrdU. Our study demonstrates that transplantation iPSC-TM stimulates proliferation of endogenous TM cells in perfusion cultured human eyes from aged donors. These data, in concert with our previous findings in animal models, suggest that functional regeneration of the TM may be possible in human eyes with primary open angle glaucoma.